Tindak Pidana Gratifikasi yang Sudah Menjadi Normalisasi Masyarakat Indonesia Ditinjau dari Aspek Budaya Hukum - Windiarti, Lisa (Proceedings Series on Social Sciences & Humanities, 2024)
The criminal act of gratification has become a widespread phenomenon and has almost normalized within Indonesian society. This normalization indicates that the acceptance of gratification is now seen as commonplace and acceptable across various aspects of life, both in the public and private sectors. From the perspective of legal culture, this reflects a significant challenge in the efforts to enforce the law and establish the moral integrity that law should uphold. Legal culture, which encompasses the values, attitudes, and perceptions of society towards law and legal institutions, plays a crucial role in either promoting or hindering corrupt behavior. This study aims to analyze how Indonesian legal culture influences societal perceptions and attitudes towards the criminal act of gratification, as well as its impact on the effectiveness of anti-gratification law enforcement. Using a qualitative approach, this research explores various cultural factors that contribute to the normalization of gratification, such as social values, traditional practices, and the lack of exemplary behavior from leaders. The findings of this study are expected to provide a deeper understanding of the interaction between legal culture and gratification practices, and to offer recommendations for more effective and sustainable law enforcement strategies to combat gratification in Indonesia.